Automatic Calibration Method for Airborne LiDAR Systems Based on Approximate Corresponding Points Model. (25th January 2022) - Tian, Yu; Zhao, Yibo; Lei, Shaogang; Ji, Chuning; Duan, Lei; Sedlák, Vladimír
Abstract : The calibration of the light detection and ranging (LiDAR) system is critical to ensure the accuracy of point data. In this paper, the lever-arm measurement of airborne LiDAR system (ALS) was realized by photogrammetry. An automatic iterative boresight calibration method based on approximate corresponding points (CPs) matching was proposed to correct the boresight misalignment. It was based on iterative closest point (ICP) registration algorithm with a normal space sampling strategy, and approximate CPs were obtained by establishing filter rules. The experimental results showed that the absolute accuracy of the calibrated ALS reached 7.13 cm when the flight altitude was 100 m, meeting the accuracy requirements.